1995
DOI: 10.1136/ard.54.5.345
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional importance of plasma kallikrein in the synovial fluids of patients with rheumatoid, psoriatic, and osteoarthritis.

Abstract: Objectives-To determine and identify, unequivocally, if plasma kallikrein (PK) is present in the synovial fluid of patients with rheumatoid (RA), psoriatic (PA) and osteo (OA) arthritis, and to consider its functional importance in the inflamed joint. Methods-Therapeutically aspirated synovial fluids (pooled and individual samples, n = 66) were obtained from patients with arthritis. In addition, serum (n = 14) was collected from RA patients, and saliva (n = 10) and urine (n = 10) from normal individuals. Enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Bradykinin and kallikrein activities have been found in the synovial fluid of patients affected by several arthropathies such as osteoarthritis, rheumatoid arthritis, gout and psoriatic arthritis. Moreover, kinin levels correlate well with the degree of joint disease (Rahman et al ., 1995; Nishimura et al ., 2002; Meini and Maggi, 2008). Bradykinin potentially affects the joint at the level of either synovium, cartilage or bone, as synovial cells, chondrocytes and osteoblasts all express the kinin B 2 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Bradykinin and kallikrein activities have been found in the synovial fluid of patients affected by several arthropathies such as osteoarthritis, rheumatoid arthritis, gout and psoriatic arthritis. Moreover, kinin levels correlate well with the degree of joint disease (Rahman et al ., 1995; Nishimura et al ., 2002; Meini and Maggi, 2008). Bradykinin potentially affects the joint at the level of either synovium, cartilage or bone, as synovial cells, chondrocytes and osteoblasts all express the kinin B 2 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, we compared the activities of kallikreins and kininogen measured simultaneously in plasma and synovial fluid from patients with inflammatory joint diseases. Recently, Rahman et al [8] elegantly identified the presence of total kallikrein and active plasma kallikrein in synovial fluid of patients with rheumatoid arthritis, psoriatic arthritis and osteoarthrosis. In our study, besides demonstrating the presence of amidase activity in synovial fluid we also observed increased levels in relation to plasma.…”
Section: Kallikrein/kininogen/inflammatory Parameter Correlationsmentioning
confidence: 98%
“…Total kininogen was studied in plasma and synovial fluid of patients with adult rheumatoid arthritis, reporting diminution of levels of HKg in synovial fluid of these patients [4]. However, plasma and tissue kallikreins have been detected separately in plasma or synovial fluid of patients with arthritis [5][6][7][8]. In this study, we compared the amidase activity of plasma and tissue kallikreins upon chromogenic substrates and kininogen levels simultaneously in plasma and synovial fluid of patients with inflammatory articular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Bradykinin plays an important role in the pathogenesis of inflammatory disease, such as rheumatoid arthritis, asthma and rhinitis [1][2][3]. Additionally, a possible role for kinins has been postulated in progressive neurodegenerative diseases such as multiple sclerosis by the transformation of the resting microglia into an active state with a macrophage-like activity [4].…”
Section: Introductionmentioning
confidence: 99%